Potential of Mobile Energy Hubs for Enhancing Resilience of Electricity Distribution Systems - Shahbazi, Amid; Aghaei, Jamshid; Niknam, Taher; Ardeshiri, Masood; Kavousi-Fard, Abdollah; Shafie-khah, Miadreza (Elsevier, 2022)
In this paper, an operational framework is presented to improve electrical distribution network resilience based on the Mobile Energy Hubs (MEHs) concept. In fact, critical loads should be immediately islanded in a post-flood state and then recovered. Accordingly, this paper focuses on providing an effective management solution to enhance the functioning of electricity distribution systems with the objective of maximizing restoration of critical loads and minimizing their restoration time span based on MEH. To this end, MEHs are installed on trucks to deliver the required power for supplying the islanded critical loads in zones affected by a flood. Besides, in order to demonstrate a practical resilient structure, possible damage inflicted on other critical infrastructures is considered. Moreover, obstacles resulting from the destruction of the transportation infrastructure caused by a flood are overcome by using the shortest path algorithm (SPA). In this case, the optimization algorithm determines the shortest possible path for transporting the MEHs to supply critical loads in the least time aiming to improve the network resilience indicators. Finally, the proposed framework is studied in a standard test electricity distribution network. Simulations are carried out to evaluate the network resilience indicators of the proposed framework in obtaining a resilient distribution network during natural disasters.
Keywords: Resilience; Distributed Generation; Short Path Algorithm; Mobile Energy Hub; Electricity distribution systems; fi=Sähkötekniikka|en=Electrical Engineering|